Agroforestry for doubling farmers’ income: a proven technology for trans-gangetic plains zone of India - Singh, Mahendra; Sridhar, K. B.; Kumar, Dhiraj; Dwivedi, R. P.; Dev, Inder; Tewari, R. K.; Chaturvedi, O. P. (Indian Farming, 2018)
The Government of India has already planned to take many measures to increase farm income, stabilize production and, consequently, improve small farm productivity. Integrated farming system approach involving synergic blending of crops, horticulture, dairy, fisheries, poultry, etc. seems viableoption to provide regular income and at site employment to small-land holder, decreasing cultivation cost through multiple use of resources and providing much needed resilience for predicted climate change scenario high-yielding varieties and hybridseeds are very essential for a successful crop production and increasing the yield by 15 to 20% depending upon the crop and it canbe further raised up to 45% with efficient management of other inputs. Micro-irrigation along with the nutrient application can be highly efficient and priority should be given to empower farmers with microirrigation. The government is aggressively promoting a new crop insurance (PMFBY) given increased challenges by farmers due to frequent climatic disturbances.